9 The Statutes at Large of South Carolina: Containing the Acts Relating to Roads, Bridges and Ferries, With an Appendix, Containing the Militia Acts Prior to 1794, at 691 (David J. McCord ed., 1841) - (:unkn) unknown (My University, 1791)
The necessary arms were revised in 1791. Firearms were "a good musket and bayonet . . . or other sufficient gun." Edged arms were "a good and sufficient small sword, broad sword, cutlass or hatchet." Along with the usual cartouch box, powder horn or flask, shot bag or pouch, spare flint, and ammunition.
Keywords: MILITIAS; DEFINITIONS